Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan dan Earning Management sebagai Variabel Moderasi - Jessica Ang; Werner Ria Murhadi; Endang Ernawati (Journal of Entrepreneurship and Business, 2020)
This study aims to analyze the effect of corporate social responsibility on a company’s financial performance with earning management as a moderating variable. The variables used in this study are corporate social responsibility, firm age, firm size, leverage, and earning management as moderation variables. This research uses a quantitative approach using multiple linear regression analysis. The target population in this study are all non-financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018, which amounted to 875 observations. The results showed that corporate social responsibility variable has no significant influence on financial performance. The analysis with moderating variables show that earning management can strengthen the relationship between corporate social responsibility and financial performance. Keywords: corporate social responsibility, financial performance, earning management